SUV39h-independent association of HP1 beta with fibrillarin-positive nucleolar regions - Horáková, Andrea Harnicarová; Bártová, Eva; Galiová, Gabriela; Uhlírová, Radka; Matula, Pavel; Kozubek, Stanislav (Chromosoma, 2010)
Heterochromatin protein 1 (HP1), which binds to sites of histone H3 lysine 9 (H3K9) methylation, is primarily responsible for gene silencing and the formation of heterochromatin. We observed that HP1 beta is located in both the chromocenters and fibrillarin-positive nucleoli interiors. However, HP1 alpha and HP1 gamma occupied fibrillarin-positive compartments to a lesser extent, corresponding to the distinct levels of HP1 subtypes at the promoter of rDNA genes. Deficiency of histone methyltransferases SUV39h and/or inhibition of histone deacetylases (HDACi) decreased HP1 beta and H3K9 trimethylation at chromocenters, but not in fibrillarin-positive regions that co-localized with RNA polymerase I. Similarly, SUV39h- and HDACi-dependent nucleolar rearrangement and inhibition of rDNA transcription did not affect the association between HP1 beta and fibrillarin. Moreover, the presence of HP1 beta in nucleoli is likely connected with transcription of ribosomal genes and with the role of fibrillarin in nucleolar processes.
Keywords: represorové proteiny; myši; Cells, Cultured; kultivované buňky; Chromosomal Proteins, Non-Histone; methyltransferasy; chromozomální proteiny, nehistonové; buněčné jadérko; zvířata; Cell Nucleolus; Mice; Protein Binding; Repressor Proteins; Fibroblasts; Methyltransferases; vazba proteinů; fibroblasty; Animals